Lipase-mediated production of 1-oleoyl-2-palmitoyl-3-linoleoylglycerol by a two-step method. (August 2020) - Gao, Liang; Cheng, Xinyi; Yu, Xuwei; Wang, Xiaosan; Jin, Qingzhe; Wang, Xingguo
Abstract: 1-Oleoyl-2-palmitoyl-3-linoleoylglycerol (OPL) is a critical structured lipid in human milk fat and it plays an important role in infants' health. The development of an efficient method for such compound preparation is necessary. In this study, one- and two-step methods for OPL production by enzymatic acidolysis of fractionated palm stearin with mixed acids were compared in solvent-free and solvent systems. The results demonstrated that in the solvent system, the OPL contents by the one- and two-step methods were 45.8% and 56.7%, respectively. In the solvent-free system, the one- and two-step methods resulted in the formation of 43.7% and 54.8% OPL, respectively. Subsequently, acidolysis conditions of the two-step method were optimized. Under the optimum conditions, the content of OPL was 57.7%, and 83.2% of palmitic acid was at the sn-2 position. The prepared OPL has potential to be applied in infant formulas. Graphical abstract: Reaction route for the two-step lipase-catalyzed production of OPL. Image 1 Highlights: 1-Oleoyl-2-palmitoyl-3-linoleoylglycerol (OPL) was enzymatically prepared. Two-step acidolysis is more effective for OPL production than one-step method. NS40086 lipase shows a good sn-1, 3 specificity in enzymatic acidolysis. Palmitic acid removal reduces the rate of backward reaction and increases OPL yield.